Video analysis of tackling situations leading to concussion in collegiate rugby union - Suzuki, K.; Nagai, S.; Ogaki, R.; Iwai, K.; Furukawa, T.; Miyakawa, S.; Takemura, M. (The Journal of Physical Fitness and Sports Medicine, 2019)
The purpose of this study was to clarify the tackling characteristics of tacklers relationship causing concussion based on match video records in the collegiate rugby union. Twenty-three tackling situations leading to concussion were identified based on injury data and video records. Additionally, 94 tackling situations in which concussion did not occur were extracted from the same matches. Overall, one hundred and seventeen tackling situations were analyzed in detail, and categorized into three tackle phases and outcomes. Logistic regression analysis was performed to clarify which tackling characteristics in the tackler relationship had a higher chance of concussion. The chance of concussion occurring to a tackler was significantly higher for collision tackle (odds ratio [OR] 84.00, 95% CI 8.27-853.11), making initial contact with tackler`s head/neck (OR 23.47, 95% CI 4.80-114.71), no arm usage by tackler (OR 3.54, 95% CI 1.23-10.20) and tackle break by ball-carrier (OR 5.76, 95% CI 1.67-19.85). Conversely, tacklers were significantly less likely to suffer concussion when the ball-carrier performed a side step before initial contact (OR 0.11, 95% CI 0.01-0.85). In conclusion, tackles leading to concussion were related to various factors in the time period before and after tackle as well as in the moment of tackle. The results of this study suggest that further research needs to be done, given the relationship between each tackling characteristic. Moreover, we consider that players and coaching staff should improve tackle skill safety by clarifying the common contributing factors to both suffering concussion and tackle performance.